Energy transfer from colloidal nanocrystals to strongly absorbing perovskites. Issue 25 (14th June 2017) - Cabrera, Yasiel; Rupich, Sara M.; Shaw, Ryan; Anand, Benoy; de Anda Villa, Manuel; Rahman, Rezwanur; Dangerfield, Aaron; Gartstein, Yuri N.; Malko, Anton V.; Chabal, Yves J.
Abstract : Hybrid quantum dot/perovskite heterostructures were prepared and resulted in highly efficient radiative and non-radiative energy transfer. Abstract : Integration of colloidal nanocrystal quantum dots (NQDs) with strongly absorbing semiconductors offers the possibility of developing optoelectronic and photonic devices with new functionalities. We examine the process of energy transfer (ET) from photoactive CdSe/ZnS core/shell NQDs into lead-halide perovskite polycrystalline films as a function of distance from the perovskite surface using time-resolved photoluminescence (TRPL) spectroscopy. We demonstrate near-field electromagnetic coupling between vastly dissimilar excitation in two materials that can reach an efficiency of 99% at room temperature. Our experimental results, combined with electrodynamics modeling, reveal the leading role of non-radiative ET at close distances, augmented by the waveguide emission coupling and light reabsorption at separations >10 nm. These results open the way to combining materials with different dimensionalities to achieve novel nanoscale architectures with improved photovoltaic and light emitting functionalities.